Chasing the storm: Recruiting non‐hospitalized patients for a multi‐site randomized controlled trial in the United States during the COVID‐19 pandemic - Kelly Hu; Jean‐Claude Tardif; Melanie Huber; Maria Daly; Aisha T. Langford; Ruth Kirby; Yves Rosenberg; Judith Hochman; Avni Joshi; Zohar Bassevitch; Michael H. Pillinger; Binita Shah (Wiley, 2022)
Abstract Randomized controlled trials (RCTs) remain the gold standard to evaluate clinical interventions, producing the highest level of evidence while minimizing potential bias. Inadequate recruitment is a commonly encountered problem that undermines the completion and generalizability of RCTs-and is even more challenging when enrolling amidst a pandemic. Here, we reflect on our experiences with virtual recruitment of non‐hospitalized patients in the United States for ColCorona, an international, multicenter, randomized, placebo‐controlled coronavirus disease 2019 (COVID‐19) drug trial. Recruitment challenges during a pandemic include constraints created by shelter‐in‐place policies and targeting enrollment according to national and local fluctuations in infection rate. Presenting a study to potential participants who are sick with COVID‐19 and may be frightened, overwhelmed, or mistrusting of clinical research remains a challenge. Strategies previously reported to improve recruitment include transparency, patient and site education, financial incentives, and person‐to‐person outreach. Active measures taken during ColCorona to optimize United States recruitment involved rapid expansion of sites, adjustment of recruitment scripts, assessing telephone calls versus text messages for initial contact with participants, institutional review board‐approved financial compensation, creating an infrastructure to systematically identify potentially eligible patients, partnering with testing sites, appealing to both self‐interest and altruism, and large‐scale media efforts with varying degrees of success.